2018
DOI: 10.1128/jvi.01130-17
|View full text |Cite
|
Sign up to set email alerts
|

Both Sphingomyelin and Cholesterol in the Host Cell Membrane Are Essential for Rubella Virus Entry

Abstract: (RuV) causes a systemic infection and transplacental fetal infection causes congenital rubella syndrome. In this study, we showed that treatment of cells with sphingomyelinase inhibited RuV infection. Assays using inhibitors of serine palmitoyl transferase and ceramide transport protein demonstrated the contribution of sphingomyelin (SM) to RuV infection. Compelling evidence for direct binding of RuV to lipid membranes at neutral pH was obtained using liposome co-flotation assays. The absence of either SM or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
(64 reference statements)
4
34
0
Order By: Relevance
“…Beyond its primary function to deliver ceramide from the ER to the Golgi apparatus, CERT participates in various biological events, including polyploid cancer cell death 32 , EGF receptor signaling 33 , lipotoxicity and glucolipotoxicity in islet β-cells 34,35 , muscle insulin signaling 36 , stress-induced Golgi disassembly 37 , protein secretions 38 , phosphoinositide turnover at the trans Golgi network 39 , cytotoxic autophagy 40 , and senescence 41 . Additionally, pharmacological or genetic inhibition of CERT negatively affects the proliferation of several types of intracellular pathogens [42][43][44][45][46] . Moreover, a point mutation causing the loss of repressive phosphorylation in the human CERT gene results in a hereditary mental development disorder with an autosomal dominant inheritance 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its primary function to deliver ceramide from the ER to the Golgi apparatus, CERT participates in various biological events, including polyploid cancer cell death 32 , EGF receptor signaling 33 , lipotoxicity and glucolipotoxicity in islet β-cells 34,35 , muscle insulin signaling 36 , stress-induced Golgi disassembly 37 , protein secretions 38 , phosphoinositide turnover at the trans Golgi network 39 , cytotoxic autophagy 40 , and senescence 41 . Additionally, pharmacological or genetic inhibition of CERT negatively affects the proliferation of several types of intracellular pathogens [42][43][44][45][46] . Moreover, a point mutation causing the loss of repressive phosphorylation in the human CERT gene results in a hereditary mental development disorder with an autosomal dominant inheritance 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that alphaviruses require membrane sphingolipids, specifically SM, as a cofactor for virus fusion (Nieva et al, 1994). Moreover, Rubella virus was shown to directly bind to SM and cholesterol/SM-enriched microdomains (Otsuki et al, 2018). Lipidomic analyses have shown an increase in the SM content of IAV-infected cells (Tanner et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…In RUBV infection experiments, recombinant RUBV rHS-p150/AG1, which expresses p150 fused with the humanized monomeric Azami green 1 (AG1) fluorescent protein, was used (21,22). In SINV infection experiments, the isolated MM2215 virus strain was used (23,24). The infected cells were cultured with various concentrations of 17-allylamino-17-desmethoxygeldanamycin , an inhibitor of HSP90 activity (25).…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant virus rHS-p150/3FLAG, expressing p150 tagged with the 3FLAG epitope, was recovered from the genomic infectious cDNA clone pHS-p150/ 3FLAG. The MM2215 strain of SINV has been reported previously (23,24). RUBV and SINV were propagated in BHK cells.…”
Section: Methodsmentioning
confidence: 99%